Highly efficient RNA-guided genome editing in human cells via delivery of purified Cas9 ribonucleoproteins - Kim, Sojung; Kim, Daesik; Cho, Seung Woo; Kim, Jungeun; Kim, Jin-Soo (Genome Research, 2014)
RNA-guided engineered nucleases (RGENs) derived from the prokaryotic adaptive immune system known as CRISPR (clustered, regularly interspaced, short palindromic repeat)/Cas (CRISPR-associated) enable genome editing in human cell lines, animals, and plants, but are limited by off-target effects and unwanted integration of DNA segments derived from plasmids encoding Cas9 and guide RNA at both on-target and off-target sites in the genome. Here, we deliver purified recombinant Cas9 protein and guide RNA into cultured human cells including hard-to-transfect fibroblasts and pluripotent stem cells. RGEN ribonucleoproteins (RNPs) induce site-specific mutations at frequencies of up to 79%, while reducing off-target mutations associated with plasmid transfection at off-target sites that differ by one or two nucleotides from on-target sites. RGEN RNPs cleave chromosomal DNA almost immediately after delivery and are degraded rapidly in cells, reducing off-target effects. Furthermore, RNP delivery is less stressful to human embryonic stem cells, producing at least twofold more colonies than does plasmid transfection.
10.1101/gr.171322.113